Catalytic Gasification of Different Pre-treated Waste Rubbers to Obtain Syngas - Norbert Miskolczi; Viktoria Zsinka; Stefania Tronci; László Urge; Laszlo Rebek (Chemical Engineering Transactions)
Waste tires represent a significant environmental burden, the further value-added use of which has not been solved. Among the energetic utilization, combustion and pyrolysis are used. During combustion, a significant amount of SOx can be released into the environment. During the pyrolysis of waste rubber, the amount of liquid product is significant, which consists of mainly aromatic and cyclic hydrocarbons. Furthermore, the sulphur content of liquid products is also significant. On the other hand, high-temperature gasification of rubber waste can be a promising solution for the production of hydrogen, synthesis gas and other hydrocarbons. During gasification, gaseous products and solid residues are produced, and the amount of liquid products is very small. The amount of hydrogen and synthesis gas can also be increased by catalysts and steam. This work focuses on the high temperature gasification of waste tires obtained by different pre-treating methods. Waste rubber samples were recycled in a laboratory scale gasifier using steam and transition metal loaded catalyst. Gases contain hydrogen and CO. The presence of steam and transition metal containing catalyst had significant effect to the product yield, however the samples pre-treating had less effect to the decomposition reactions. The thermal decomposition of raw materials was also followed by mathematical calculations. Keywords: waste tire, gasification, hyd